Non-essential role for cilia in coordinating precise alignment of lens fibres - Sugiyama, Yuki; Shelley, Elizabeth J; Yoder, Bradley K; Kozmik, Zbynek; May-Simera, Helen L; Beales, Philip L; Lovicu, Frank J; McAvoy, John W (Mechanisms of development, 2016)
The primary cilium, a microtubule-based organelle found in most cells, is a centre for mechano-sensing fluid movement and cellular signalling, notably through the Hedgehog pathway. We recently found that each lens fibre cell has an apically situated primary cilium that is polarised to the side of the cell facing the anterior pole of the lens. The direction of polarity is similar in neighbouring cells so that in the global view, lens fibres exhibit planar cell polarity (PCP) along the equatorial-anterior polar axis. Ciliogenesis has been associated with the establishment of PCP, although the exact relationship between PCP and the role of cilia is still controversial. To test the hypothesis that the primary cilia have a role in coordinating the precise alignment/orientation of the fibre cells, IFT88, a key component of the intraflagellar transport (IFT) complex, was removed specifically from the lens at different developmental stages using several lens-specific Cre-expressing mouse lines (MLR10- and LR-Cre). Irrespective of which Cre-line was adopted, both demonstrated that in IFT88-depleted cells, the ciliary axoneme was absent or substantially shortened, confirming the disruption of primary cilia formation. However no obvious histological defects were detected even when IFT88 was removed from the lens placode as early as E9.5. Specifically, the lens fibres aligned/oriented towards the poles to form the characteristic Y-shaped sutures as normal. Consistent with this, in primary lens epithelial explants prepared from these conditional knockout mouse lenses, the basal bodies still showed polarised localisation at the apical surface of elongating cells upon FGF-induced fibre differentiation. We further investigated the lens phenotype in knockouts of Bardet-Biedl Syndrome (BBS) proteins 4 and 8, the components of the BBSome complex which modulate ciliary function. In these BBS4 and 8 knockout lenses, again we found the pattern of the anterior sutures formed by the apical tips of elongating/migrating fibres were comparable to the control lenses. Taken together, these results indicate that primary cilia do not play an essential role in the precise cellular alignment/orientation of fibre cells. Thus, it appears that in the lens cilia are not required to establish PCP.
Keywords: oční čočka; Lens; Animals; IFT88; Bardet–Biedl Syndrome (BBS); Cilia; Mice, Knockout; nádorové supresorové proteiny; myši knockoutované; cilie; cytoskeletální proteiny; Lens, Crystalline; Epithelial Cells; kultivované buňky; proteiny asociované s mikrotubuly; Cells, Cultured; Cytoskeletal Proteins; polarita buněk; Tumor Suppressor Proteins; Planar cell polarity (PCP); Cell Polarity; Microtubule-Associated Proteins; zvířata; epitelové buňky; Primary cilium